Ultrasonographic features of IgG4-related kidney disease: diagnostic value and correlation with clinical-pathological findings - Wei, Boxiong; Liu, Yi; Wang, Suxia; Shao, Yuhong; Sun, Xiuming; Chen, Luzeng; Zhang, Xiumei (Frontiers in Medicine, 2025)
ObjectiveTo systematically characterize the ultrasonographic features of biopsy-proven IgG4-related kidney disease (IgG4-RKD) and to evaluate their correlation with key clinicopathological parameters.MethodsIn this retrospective study, the ultrasonographic, clinical, laboratory, and pathological data of 15 patients with biopsy-confirmed IgG4-RKD were analyzed. Key sonographic features, including renal size, parenchymal echotexture, focal lesions, and resistive index, were evaluated and correlated with clinicopathological findings.ResultsThe cohort consisted of predominantly older males (86.7%) with frequent multi-organ involvement (60.0%). The most common ultrasonographic pattern included bilateral involvement (93.3%), increased or heterogeneous echogenicity (73.3%/60.0%), multiple hypoechoic areas (46.7%), and enlargement of at least one kidney (>12 cm) in 40.0% of patients. Increased renal length showed a significant positive correlation with serum IgG4 levels (r = 0.63, 95% confidence interval (CI) [0.17, 0.86], p < 0.05), and parenchymal thickness showed a significant negative correlation with serum C3 levels (r = −0.58, 95% CI [−0.84, −0.10], p < 0.05). Furthermore, parenchymal thickness was moderately correlated with serum creatinine (r = 0.51, n = 15, 95% CI [0.00, 0.81], p < 0.05). Ultrasound also effectively monitored therapeutic response, with 83.3% of followed patients showing structural improvement.ConclusionUltrasonography in IgG4-RKD reveals a characteristic pattern of findings that not only serve a descriptive role but also quantitatively correlate with serological disease activity and renal dysfunction. Therefore, ultrasound is a valuable, non-invasive tool for initial assessment, guiding diagnosis, and monitoring therapeutic response in the clinical management of IgG4-RKD.